Isolation and characterization of Schleiferilactobacillus harbinensis GX0002947 from naturally fermented sour porridge and its application in cereal fermentation - Liu, Guofang; Man, Yuanyuan; Tian, Hongmei; Wu, Liuyan; Li, Qiao; Jiang, Mingguo; Dou, Jin; Su, Huizhao (Frontiers in Microbiology, 2025)
Sour porridge, a fermented food from the Guangxi Zhuang Autonomous Region of China, contains an abundance of lactic acid bacteria and has high nutritional value. In this study, a strain of Schleiferilactobacillus harbinensis GX0002947 was isolated from naturally fermented sour porridge from Fusui County, Chongzuo City, Guangxi Zhuang Autonomous Region of China. The strain was highly effective in the fermentation of sour porridge. It was found that strain S. harbinensis GX0002947 showed good acid and bile salt resistance at pH 3.5, bile salt concentration of 0.3 g/100 mL, in artificial gastrointestinal fluids, and the bacterial population density was greater than 106 CFU/mL. The fermentation broth and culture supernatant of strain S. harbinensis GX0002947 showed effective antibacterial activity against the foodborne pathogens Escherichia coli, Staphylococcus aureus, and Bacillus cereus. The optimum fermentation process for sour porridge was found to consist of a fermentation temperature of 37°C, inoculation dose of 12.5%, and fermentation time of 96 h, resulting in a total protein content of 397.33 μg/mL and a total amino acid content of 629.63 μmol/mL in the sour porridge. In addition, the community diversity of fermented sour porridge was explored by high-throughput Illumina sequencing. The results showed that fermentation of sour porridge by S. harbinensis GX0002947 resulted in the formation of a unique microbial community. Metabolites were compared between sour porridge fermented by strain S. harbinensis GX0002947 and naturally fermented sour porridge and were analyzed by LC–MS. This identified 24 differential metabolites which primarily included amino acids, carbohydrates, and lipids, suggesting that the associated pathways played a key role in the fermentation of sour porridge by S. harbinensis GX0002947. In conclusion, this study used inoculation of lactic acid bacteria for the fermentation of sour porridge, and assessed differences in microbial community structure and metabolites after inoculation with S. harbinensis GX0002947. These findings provided a theoretical basis and technical support for sour porridge production.